The Enduring Flame: Stress, Epigenetics, and the California Indian 1769-2000. - GONZALEZ, MICHAEL (American Indian Quarterly)
Epigenetics, the study of how life's challenges can alter the body's physiology, illustrates the ways stress harmed California's Mission Indians and may still harm their descendants. Eyewitness accounts from the mission period and entries for causes of death in burial records suggest that stress compromised the immune system for many Indians and made others more likely to kill themselves, commit acts of domestic violence, or suffer from mental illness. These ailments do not remain confined to one moment in time. As epigenetics proposes, stress can become encoded in the body. When modern Indians face the same pressures as did their ancestors, the chances increase that age-old afflictions will persist.